The last September : a novel - Gramont, Nina de (Algonquin Books of Chapel Hill, 2015)
Brett has been in love with Charlie ever since he took her skiing on a lovely Colorado night fourteen years ago. And now, living in a seaside cottage on Cape Cod with their young daughter, it looks as if they have settled into the life they desired. However, Brett and Charlie's marriage has been tenuous for quite some time. When Charlie's unstable younger brother plans to move in with them, the tension simmering under the surface of their marriage boils over.